Asha: Using a mobile game to educate, support and monitor the medical adherence of children diagnosed with HIV - Whittaker, Dominique (My University, 2019)
The focus of this research is in the area of using a designed pedagogical model, called the Educational Game Creation and Assessment Model (EGCAM), to inform the design decisions made to create the mobile game Asha to serve the needs of HIV positive children between the ages of 8 to 12. Asha does this by attempting to educate, support and monitor the medical adherence of the user through its gameplay. Such a study plays an important role due to the noted practice of parents of HIV positive children not involving them in their diagnoses or treatment due to the stigma that surrounds the disease. The research approach adopted in this dissertation includes creating and documenting the development process of the game Asha with an end result of conducting an informal qualitative play testing session whereby children that fell within the target market provided feedback on the game. The findings from this research provide evidence that the use of a mobile game is a viable means of educating children as results were positive and found the participants saying they learnt something new and would play the game again. The main conclusions drawn from this study are incomplete due to the small test group that was available. However, results do indicate a positive response to the use of the EGCAM model to create the game Asha as well as the use of said game having potential to be successful in its intended final outcome. This dissertation recommends that with the use of educational and serious games in other disciplines, a larger audience can be reached and their needs served.
dissertation resubmitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Game Design, Johannesburg, 2019
Keywords: Educational technology; Educational games--Design and construction